A Preliminary Contribution to The Flora of Rajpipla Forests in Gujarat State - Shah, G. L. (Indian Forester, 1967)
As far as the author is aware there is no earlier report on the Flora of Rajpipla forests. The present paper, therefore, is prepared on the basis of plants collected from Ghantoli, Dediapada, Kokam and Dumkhal forests in December, 1965. In all about 203 plants are listed of which 179 ars dicotyledons and 24 monocotyledons.